Persistence of Clostridium difficile RT 237 infection in a Western Australian piggery. (February 2016) - Moono, Peter; Putsathit, Papanin; Knight, Daniel R.; Squire, Michele M.; Hampson, David J.; Foster, Niki F.; Riley, Thomas V.
Abstract: Clostridium difficile is commonly associated with healthcare-related infections in humans, and is an emerging pathogen in food animal species. There is potential for transmission of C. difficile from animals or animal products to humans. This study aimed to determine if C. difficile RT 237 had persisted in a Western Australian piggery or if there had been a temporal change in C. difficile diversity. C. difficile carriage in litters with and without diarrhea was investigated, as was the acquisition of C. difficile over time using cohort surveys. Rectal swabs were obtained from piglets aged 1–10 days to determine prevalence of C. difficile carriage and samples were obtained from 20 piglets on days 1, 7, 13, 20, and 42 of life to determine duration of shedding. Isolation of C. difficile from feces was achieved by selective enrichment culture. All isolates were characterized by standard molecular typing. Antimicrobial susceptibility testing was performed on selected isolates ( n   =  29). Diarrheic piglets were more likely to shed C. difficile than the non-diseased ( p  =  0.0124, χ2 ). In the cohort study, C. difficile was isolated from 40% samples on day 1, 50% on day 7, 20% on day 13, and 0% on days 20 and 42. All isolates were RT 237 and no antimicrobial resistance was detected. The decline of shedding of C. difficile to zero has public health implications because slaughter age pigs have a low likelihood of spreading C. difficile to consumers via pig meat. Highlights: We describe the epidemiology of Clostridium difficile in a Western Australia piggery. We have demonstrated a relationship between age of piglets and fecal shedding of C. difficile . We have shown that ribotype 237 has persisted in one piggery in Western Australia for over six years.